A case study in psychology education: How student have a problem solving skills? - Toharudin, Uus; Kurniawan, Iwan Setia (University of Muhammadiyah Malang, 2017)
This study aims to determine the ability of problem solving student of biology and perceptions in the subject of educational psychology, using descriptive quantitative research method. The samples in this study were 30 students for the experimental group-1 and 30 students for the experimental group-2 group. Data was analyzed using descriptive statistical. The results showed that problem solving ability biology student teachers in educational psychology courses including both categories for the experimental group and category-1 enough for the experimental group-2. It is inversely related to the acquisition of the average score of the test result is the average score of the experimental group-1 amounted to 2.92, and the average score of the experimental group-2 at 3.11. The results of the questionnaire analysis of student perceptions obtained the highest score of 3.30, or by 82.5% said the ability of the faculty in presenting the material in an interesting way. While the lowest score of 2.50 or a 62.5% state that faculty lectures begin and end on time, and the availability of lecturers in providing guidance outside the lecture. Based on the results of the study it can be concluded that the experimental group problem solving ability-one better than the experimental group-2.